Inclusion-Exclusion Dynamics: A Comparative Study of Nepal’s National Anthems “ShreemanGambhira” and “SayaunThunga” - Dhungel, Nabaraj (Patan Pragya, 2020)
This article attempts to critically analyze the inclusion-exclusion dynamics in two Nepalese National anthems “Shreeman Gambhira” and “Sayaun Thunga” using Michel Foucault’s ideas of social inclusion and exclusion. It explores how the old national anthem and the new national anthem of Nepal picturize such dynamicsin melodious tunes. It also projects how the former deifies the monarchs and monarchy, and the latter glorifies the sacrificial contribution of the Nepalese people from diverse nationalities and geographical regions. This research shows that the former, military tune-changed king’s song ultimately turned out to be national anthem, centers on the monarchy singularly focusing on the longevity, sovereignty, ancestral glory, grandeur and supremacy of the king only excluding the pluralistic voice of the nation and people whereas the latter represents the nation and people highlighting the unity in diversity, people’s and nation’s sovereignty and longevity, equality, people’s democracy, inclusiveness and proportional representation as it is the achievement of People’s War of ten years and People’s Movement II. The old one promotes the exclusionary philosophy whereas the new one the inclusionary philosophy of true patriotism and humanism voicing even the voiceless people. This study clearly reveals how the nation-and-people representing national anthems can be both inclusionary according to the political necessity after the people’s movement and the political interest and exclusionary concealed in the melodious tune and deceptive voice of patriotism. The research is significant for critical analysts to look at the exclusion within inclusion and inclusion within exclusion even in the national anthems and patriotic structures which can be only the discourses.